Flowing between gongs: Mixed-methods insights into shared flow and temporal distortion in music performance - Hannah J. Gibbs; Andrea Schiavio (PLoS ONE, 2025)
Ideas of temporal distortion prevail in the discourse of flow research, where references are often made to “time flying”. Nonetheless, little research has investigated how flow affects time perception in terms of both directionality and surrounding context, particularly within shared flow. Simultaneously, temporal distortion during music listening has been explored, but little is known about how time is experienced by performers. With this in mind, we aimed to investigate whether time distortion is associated with the experience of shared flow state, and the awareness participants have towards influencing factors on such experiences, in the context of music performance. Four groups of Javanese gamelan ensembles (total N = 36, age in years M = 44.83, SD = 14.993, 47.2% female), played in three conditions. We collected qualitative and quantitative data; focus groups and follow-up surveys explored understandings of shared flow and time, while questionnaires included pre-validated scales and an item requiring participants to estimate how much time they thought had passed. Qualitative and mixed methods findings suggest an optimal middle ground of conditions for “time flying” to occur, akin to flow state. Meanwhile, quantitative results indicate a complex relationship between temporal distortion and shared flow, whereby the relationships are opposed under two shared flow factors.